Islamic banking in Libya: emergence, growth, and prospects - A.S. Abusloum, Mahmoud; Ahmad, Khaliq; Bello, Nabil (IGI Global Publishing, 2020)
This chapter identifies the internal and external challenges for Islamic banking in Libya. It is a conceptual work using secondary data where relevant concepts in terms of challenges of the conversion process in Libya were demonstrated. Conversion process is surrounded and faced by many challenges. Internal challenges are not less significant than external ones. Trained human resource, lack of awareness in Islamic banking, and resistance to change to Islamic banks are considered as internal challenges which represent the stage of readiness to convert the sector. On the other hand, the economic structure, the political situation, and the regulatory framework hinder the process externally. This implies that stakeholders should come up with comprehensive strategies and plans about the conversion process which will improve the readiness level of the banks, raise the awareness and willingness of their employees, and increase the skills of banks’ staff.